STRATEGIC ROLES OF AGRICULTURAL EXTENSION AGENTS AND INFORMATION TECHNOLOGY UTILIZATION IN RICE FARMER GROUP DEVELOPMENT IN TELUK KECAPI OGAN ILIR - Eka Mulyana; Yulia Sari; Merna Ayu Sulastri; Alisyah Futri (LPPM Universitas Malikussaleh - Indonesia, 2026)
Digital transformation in agricultural sector has accelerated the shift toward more adaptive and technology-based agricultural extension systems. Agricultural extension is a strategic role in supporting farmer group development. This study aimed to analyze the role of agricultural extension workers, the utilization of information technology, extension competency, and their relationship with the development of rice farmer groups in Teluk Kecapi Village, Pemulutan District, Ogan Ilir Regency, South Sumatra, Indonesia. The study employed a survey method using Simple Random Sampling techniques involving members of rice farmer groups. Data were collected through structured interviews and questionnaires and analyzed using Likert Scale analysis and Spearman Rank Correlation. The findings revealed that the roles of agricultural extension workers, information technology utilization, extension competency, and farmer group development were categorized as high. Extension workers were perceived as actively facilitating agricultural information dissemination, digital communication, institutional strengthening, and farmer capacity development. The results further indicated that the roles of extension workers, digital platforms, digital content, personal attributes, and extension knowledge had positive and significant relationships with farmer group development. The study highlights that the integration of extension competency and digital technology utilization constitutes a critical factor in promoting more effective, adaptive, and sustainable farmer group development. Keywords: Agricultural Extension, Digital Extension, Extension Competency, Farmer Groups, Information Technology.